Peran Health Care Administrator dalam Menyusun Strategi Peningkatan Indeks Kepuasan Pasien pada Layanan Rawat Jalan Digital - Erni Susilawati (Lembaga Pengembangan Kinerja Dosen, 2025)
Digital outpatient services are an important alternative in providing fast, efficient, and affordable health services, especially after the COVID-19 pandemic. However, this system change requires an active role from Health Care Administrators in designing strategies that can maintain and improve patient satisfaction. This article aims to analyze how the role of health administrators in developing technology-based quality management strategies to optimize patient experience in digital services. This study uses a qualitative approach with literature studies and analysis of digital outpatient service policies. The results of the study indicate that the success of increasing the patient satisfaction index depends on the administrator's ability to design effective digital communication strategies, virtual queue management, digital HR training, and strengthening online feedback systems. The involvement of administrators in strategic decision-making also makes a major contribution to improving service quality. The main recommendation of this study is the need to strengthen the capacity of health administrators in aspects of information technology, digital risk management, and patient engagement. With this strategic role, health administrators are at the forefront of the transformation of digital health services in the future.